If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = 3x Reorder the terms: -8 + 6x = 3x Solving -8 + 6x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -8 + 6x + -3x = 3x + -3x Combine like terms: 6x + -3x = 3x -8 + 3x = 3x + -3x Combine like terms: 3x + -3x = 0 -8 + 3x = 0 Add '8' to each side of the equation. -8 + 8 + 3x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 3x = 0 + 8 3x = 0 + 8 Combine like terms: 0 + 8 = 8 3x = 8 Divide each side by '3'. x = 2.666666667 Simplifying x = 2.666666667
| 1x-9= | | 4x-y=-10 | | t(t-2)-3t(t-2)=0 | | t(t-2)-3t(t-3)=0 | | 6(-x+4)=9 | | -2(5y+1)=4(y+6)-2 | | h=-16t^2+68t | | 5y+5=2y+10 | | 64=2(5x+2)+(3x-2) | | 2a^2-81=0 | | 1x+3x+-18x=0 | | 5x=2-2x | | x-3x+-18x=0 | | -4x^2+3x=1 | | 3(h)+6=2(h)-14 | | 3(-20)+6=2(-20)-14 | | 3x-2y+5z+au=0 | | -4x-5x=18 | | 6n^2=15+12n | | 2-4(-6)-7=3+2(-6)+4 | | 12w-5=19+6w | | 4m^2-57=7m | | 10x^2+9=379 | | -2x^2+2=3x | | 11x=8x-15-6x | | 3p^2+6=216 | | 8y-7=y | | -100=109r+118 | | b(b+1)=2b+1+5 | | 4y+8=2y-14 | | (a-b)x=5 | | 4a-20=3a |